2019
DOI: 10.3390/d11120241
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Agrochemical Treatments in Agroecosystems Can Modify the Effects of Pendimethalin-Based Herbicide Exposure on Immunocompetence of a Beneficial Ground Beetle

Abstract: Herbicide application for pest control can negatively affect soil biodiversity, mainly acting on species that are involved in ecosystem service. In this study, field and laboratory trials were designed to assay herbicide exposure effects on the constitutive immunity of Harpalus (Pseudoophonus) rufipes (De Geer, 1774), a beneficial carabid species that inhabits croplands. The circulating hemocytes (THCs) and plasmatic levels of basal and total phenoloxidase (PO), as well as lysozyme-like enzyme activities, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 78 publications
(98 reference statements)
0
13
0
Order By: Relevance
“…Moreover, a previous study on the ground beetle Harpalus rufipes has been revealed a reduction in circulating phenoloxidase levels after exposure to PND field rate (Giglio et al 2019). In addition, gut microbiota takes part in endocrine system regulation, being involved in development and growth processes, as observed for honey bees and red palm weevil (Habineza et al 2019;Zheng et al 2017).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, a previous study on the ground beetle Harpalus rufipes has been revealed a reduction in circulating phenoloxidase levels after exposure to PND field rate (Giglio et al 2019). In addition, gut microbiota takes part in endocrine system regulation, being involved in development and growth processes, as observed for honey bees and red palm weevil (Habineza et al 2019;Zheng et al 2017).…”
Section: Discussionmentioning
confidence: 95%
“…However, carabids inhabiting agricultural landscapes are exposed, by direct contact or consuming contaminated food, to residual doses of agrochemicals that have sublethal effects on morphology, physiology and behaviour of organisms (Benítez et al 2018;Kunkel et al 2001;Tooming et al 2017;Van Toor, 2006) and consequently considerable effects on the diversity and abundance of species (De Heij & Willenborg, 2020;Holland & Luff, 2000). Some studies have also been provided evidence that the exposure to herbicides causes mortality or sublethal effects in carabids (Brust, 1990;Cavaliere et al 2019;Cobb et al 2007;Giglio et al 2019;Kegel, 1989;Michalková & Pekár, 2009;Prosser et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study on white shrimps (Litopenaeus vannamei) it was found that expression level of the screened lysozyme was elevated in most of (albeit not in the last few) post-larval stages compared to adults (Gollas-Galvan et al, 2017), indicating a dynamic change in lysozyme availability, with a peak during the subadult stages. Notably, energetic costs of reproduction were found to be negatively linked to lytic activity in the carabid beetle Carabus lefebvrei, where mated individuals showed dramatically decreased lytic activity in comparison to virgin individuals (Giglio et al, 2016), showing that not only maturation, but reproduction too can deteriorate the efficiency of this immune function. Indeed, we found that in mated females collected during late summer, bacterial growth inhibition power and cell wall lytic activity were lower than in virgin females, indicating that the cost of reproduction is relatively higher (or, at least, more pronounced) in late summer females.…”
Section: Discussionmentioning
confidence: 99%
“…An important, emerging threat for insect biodiversity is posed by the widespread contamination of ecosystems with plant protection chemicals, such as fertilizers, pesticides, and herbicides, which ultimately cause a rapid decline in both insect biomass and diversity [11,12]. In this Special Issue, an article by Giglio et al [13] examined this aspect. By way of combined field and laboratory trials, these authors tested the effects of exposure to realistic doses of pendimethalin-based herbicides on the constitutive immunity of Harpalus (Pseudoophonus) rufipes, a beneficial carabid species that inhabits croplands.…”
mentioning
confidence: 99%